Flexible hard nano ultrathin coating for continuous stamping of metal bipolar plate and preparation method of flexible hard nano ultrathin coating

By forming a flexible hard nano-thin coating on the metal bipolar plate, the problems of corrosion and wear of the bipolar plate surface in fuel cells are solved, and higher wear and corrosion resistance is achieved, which extends the service life of the system and reduces cost and safety risks.

CN119506813APending Publication Date: 2025-02-25BEIJING SCI & TECH PATENT OFFICE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411877959.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In fuel cells, the surface of the metal bipolar plate is susceptible to corrosion and wear, resulting in a shortening of the system's service life, and it is difficult for existing hard coating materials to maintain wear resistance and corrosion resistance in humid environments.

Method used

The flexible hard nano-thin coating preparation method of continuous stamping of metal bipolar plates is used to prepare the surface pretreatment of the metal bipolar plate substrate to form an injection layer and a nanolayer containing Ti elements, with a thickness of between 50 and 200 nm. The Ti nanolayer is prepared by high-power pulse sputtering technology to form a dense multi-layer coating.

Benefits of technology

It realizes effective protection of the surface of metal bipolar plates, improves wear resistance and corrosion resistance, enhances mechanical strength and conductivity, extends the service life of the system, and reduces cost and safety risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506813A_ABST
    Figure CN119506813A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible hard nano ultrathin coating for continuous stamping of a metal bipolar plate and a preparation method. The preparation method comprises the step of carrying out surface pretreatment on a substrate of the metal bipolar plate. Loading the sample into a forevacuum chamber through sample loading equipment to obtain high-density and high-energy Ti plasmas to bombard the surface of the polar plate so as to form a metal Ti injection layer with the thickness of 5-20 nm; changing the high-power pulse parameter sputtering power to be 5-10kW and the pulse width to be 2-10s, reducing ion energy, obtaining high-density plasma with low ion energy, preparing a T nano layer, and forming a metal T layer; and feeding the metal bipolar plate substrate of the metal T layer into a vacuum chamber to prepare the flexible hard nano multilayer coating. According to the method, the performance of the coating can be accurately controlled by regulating and controlling parameters of micro-pulses, the deposition rate is high, operation is easy and convenient, and cost is low. In addition, flammable and explosive acetylene gas is not adopted in the method, so that the method is safer and more reliable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano ultra-thin coatings, and in particular to a flexible hard nano ultra-thin coating and a preparation method thereof. Background Art

[0002] In fuel cells, bipolar plates are not only responsible for conducting electrons, but also have the important task of distributing reaction gases and removing water vapor. Therefore, these plates must have good electrical conductivity, corrosion resistance and a certain mechanical strength. They are usually made of metals such as stainless steel or aluminum alloys. Although these materials have good strength and conductivity, their surfaces are susceptible to corrosion, especially in the humid environment of fuel cells. In addition, these metals may suffer from wear during operation, which shortens the service life of the entire system. However, the problems of corrosion and wear on metal surfaces have always plagued the development of this field.

[0003] An ultra-thin nanoscale hard coating is prepared on the metal surface. This coating not only needs to have excellent wear resistance and corrosion resistance, but also must have a certain flexibility to adapt to the mechanical deformation of the bipolar plate in practical applications. At present, common hard coating materials include titanium carbide (TiC), titanium nitride (TiN) and aluminum nitride (AlN). These materials not only have high hardness, but also good chemical stability, and can effectively protect the metal substrate from corrosion and wear. How to evenly deposit these nanoscale hard materials on the metal surface to form an ultra-thin and dense coating, so it is necessary to set up a flexible hard nano-ultra-thin coating for continuous stamping of metal bipolar plates and its preparation method. Summary of the invention

[0004] The purpose of the present invention is to provide a flexible hard nano ultra-thin coating for continuous stamping of a metal bipolar plate and a preparation method thereof.

[0005] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0006] The present invention comprises the following steps:

[0007] (1) Surface pretreatment of the metal bipolar plate substrate.

[0008] (2) Loading the sample into the pre-vacuum chamber through the sample loading device, obtaining high-density, high-energy Ti plasma to bombard the surface of the electrode plate, forming a metal Ti injection layer with a thickness of 5-20nm;

[0009] (3) changing the high-power pulse parameters to sputtering power of 5 to 10 kW and pulse width of 2 to 10 s, while reducing the ion energy to obtain a high-density plasma with low ion energy, prepare a Ti nanolayer, and form a metallic Ti layer;

[0010] (4) The metal Ti layer metal bipolar plate substrate is sent into a vacuum chamber to prepare a flexible hard nano multilayer coating.

[0011] Furthermore, the surface pretreatment includes ultrasonic cleaning of the metal bipolar plate, and after cleaning for 10 to 30 minutes, the metal bipolar plate is taken out and dried with nitrogen.

[0012] Furthermore, in step (2), the argon gas pressure is adjusted to 0.1-3 Pa, the flow rate is adjusted to 20-150 sccm, and the pulse parameters are adjusted to 2-10 s.

[0013] Furthermore, in step (3), the gas pressure is adjusted to 0.3-1.5 Pa, the argon gas flow rate is 60-150 sccm, the nitrogen gas flow rate is 20-60 sccm, the pulse parameters are 5-10 kW, and the pulse width is 2-10 μs.

[0014] Furthermore, in step (2) and step (3), the power is 5 to 10 W.

[0015] Furthermore, in step (3), the nitrogen pressure is 0.1Pa to 0.15Pa, and the argon / nitrogen ratio is 4:1 to 8:1.

[0016] A flexible hard nano ultra-thin coating comprises a metal bipolar plate substrate, on which an injection layer and a nano layer containing an intermediate phase or compound formed by a Ti element are arranged.

[0017] Furthermore, the injection layer and the nanolayer have a thickness of 50 to 200 nm.

[0018] The beneficial effects of the present invention are:

[0019] The present invention is a flexible hard nano ultra-thin coating for continuous stamping of a metal bipolar plate and a preparation method thereof. Compared with the prior art, the present invention has the following technical effects:

[0020] 1. This method can accurately control the properties of the coating by adjusting the parameters of the micro-pulse, with a fast deposition rate, simple operation and low cost. In addition, this method does not use flammable and explosive acetylene gas, which is safer and more reliable.

[0021] 2. This method can accurately control the properties of the coating by adjusting the parameters of the micro-pulse, with a fast deposition rate, simple operation and low cost. In addition, this method does not use flammable and explosive acetylene gas, which is safer and more reliable. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of two technical routes for continuous stamping of flexible hard nano-thin coatings for metal bipolar plates

[0023] Figure 2This is a schematic diagram of a micron indentation photograph of a flexible hard nano-ultra-thin coating continuously stamped by a metal bipolar plate of the present invention under a load of 10-50g.

[0024] Figure 3 The graph of nano-hardness and fracture toughness changes of a flexible hard nano-ultra-thin coating continuously stamped by a metal bipolar plate of the present invention when the sputtering power increases by 3-10kW DETAILED DESCRIPTION

[0025] The present invention is further described below with specific examples. The illustrative examples and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0026] The present invention provides a method for preparing a flexible hard nano ultra-thin coating for continuous stamping of a metal bipolar plate, comprising the following steps:

[0027] like Figure 1 As shown, the present invention comprises the following steps:

[0028] (5) Surface pretreatment of the metal bipolar plate substrate.

[0029] (6) Loading the sample into the pre-vacuum chamber through the sample loading device, obtaining high-density, high-energy Ti plasma to bombard the surface of the electrode, forming a metal Ti injection layer with a thickness of 5 to 20 nm;

[0030] (7) changing the high-power pulse parameters to sputtering power of 5 to 10 kW and pulse width of 2 to 10 μs, while reducing the ion energy to obtain a high-density plasma with low ion energy, prepare a Ti nanolayer, and form a metallic Ti layer;

[0031] (8) The metal Ti layer metal bipolar plate substrate is sent into a vacuum chamber to prepare a flexible hard nano multilayer coating.

[0032] In this embodiment, the surface pretreatment includes ultrasonic cleaning of the metal bipolar plate. After cleaning for 10 to 30 minutes, the surface of the metal bipolar plate is taken out and dried with nitrogen.

[0033] In this embodiment, in step (2), the argon gas pressure is adjusted to 0.1-3 Pa, the flow rate is adjusted to 20-150 sccm, and the pulse parameters are adjusted to 2-10 μs.

[0034] In this embodiment, in step (3), the gas pressure is adjusted to 0.3-1.5 Pa, the argon gas flow rate is 60-150 sccm, the nitrogen gas flow rate is 20-60 sccm, the pulse parameters are 5-10 kW, and the pulse width is 2-10 μs.

[0035] In this embodiment, in step (2) and step (3), the power is 5 to 10 W.

[0036] In this embodiment, in step (3), the nitrogen pressure is 0.1Pa to 0.15Pa, and the argon / nitrogen ratio is 4:1 to 8:1.

[0037] A flexible hard nano ultra-thin coating comprises a metal bipolar plate substrate, on which an injection layer and a nano layer containing an intermediate phase or compound formed by a Ti element are arranged, and the material of the metal bipolar plate is 304, 316L stainless steel or a titanium alloy bipolar plate.

[0038] In this embodiment, the micron indentation of the coating under a load of 10 to 50 g is as follows: Figure 2 As shown, the thickness of the injection layer and the nano layer is 50-200 nm.

[0039] Case Study 1: Pre-coating Stamping Process for Metal Bipolar Plates

[0040] Implementation steps:

[0041] Using an ultrasonic cleaner, immerse the metal bipolar plate in alcohol and clean it for 20 minutes; blow dry the surface of the bipolar plate with nitrogen.

[0042] Plasma bombardment:

[0043] The bipolar plate was placed in a pre-vacuum chamber, and the argon pressure was adjusted to 1 Pa, the flow rate to 100 sccm, and the pulse parameters to 5 μs; a 10 nm thick metal Ti injection layer was formed.

[0044] Sputtering deposition:

[0045] Change the sputtering power to 7 kW and the pulse width to 5 μs.

[0046] The ion energy was reduced to prepare a Ti nanolayer, forming a metallic Ti layer with a total thickness of 100 nm.

[0047] Multi-layer coating preparation:

[0048] The bipolar plate was sent into the vacuum chamber, and the gas pressure was adjusted to 1 Pa, the argon flow rate to 120 sccm, the nitrogen flow rate to 40 sccm, the pulse parameters to 7 kW, and the pulse width to 5 μs.

[0049] Prepare smooth and dense flexible hard nano multilayer coatings.

[0050] Stamping:

[0051] The coated bipolar plates are stamped to meet specific mechanical component requirements and quality inspected to ensure coating integrity and product performance.

[0052] Case study 2: Coating process of metal bipolar plates after stamping

[0053] Implementation steps:

[0054] First, the metal bipolar plates are stamped and formed to meet specific mechanical component requirements;

[0055] Use an ultrasonic cleaner to immerse the stamped bipolar plate in alcohol for 15 minutes for cleaning; blow dry the surface of the bipolar plate with nitrogen.

[0056] Plasma bombardment:

[0057] The bipolar plate was placed in a pre-vacuum chamber, and the argon pressure was adjusted to 0.5 Pa, the flow rate to 80 sccm, and the pulse parameters to 3 μs to form an 8 nm thick metal Ti injection layer.

[0058] Sputtering deposition:

[0059] Change the sputtering power to 6 kW and the pulse width to 4 μs.

[0060] The ion energy was reduced to prepare a Ti nanolayer, forming a metallic Ti layer with a total thickness of 80 nm.

[0061] Multi-layer coating preparation:

[0062] The bipolar plate was sent into the vacuum chamber, and the gas pressure was adjusted to 0.8 Pa, the argon flow rate to 100 sccm, the nitrogen flow rate to 30 sccm, the pulse parameters to 6 kW, and the pulse width to 4 μs.

[0063] Prepare smooth and dense flexible hard nano multilayer coatings.

[0064] Table 1 Contact resistance and corrosion current density of coating before and after stamping

[0065] Coating status <![CDATA[Contact resistance / mΩcm 2 > <![CDATA[Corrosion current density / A cm -2 > Surface quality Before stamping 1.9-4.6 0.09-0.12 Smooth and dense After stamping 2.1-4.9 0.11-0.13 Smooth, dense, no cracks

[0066] The method for continuously preparing a flexible hard multilayer nano coating comprises a 4-target unbalanced magnetron sputtering system, a magnetron sputtering power supply (a high-power pulsed magnetron sputtering power supply, a deep oscillation magnetron sputtering power supply and a pulsed magnetron sputtering power supply), a vacuum control system, a gas circuit control system, a bias power supply, a sample stage auxiliary control system, a pre-vacuum chamber and a sample loading and unloading system. The 4-target unbalanced magnetron sputtering system is coupled with a pulsed magnetron sputtering power supply to form a plasma source. By adjusting the vacuum control system and the gas circuit control system, the optimal matching of the working gas pressure, gas flow and pulsed power supply parameters is achieved to obtain a high target material ionization rate and a high-density plasma, and high-quality nano coating materials can be prepared. All process flows are controlled by a computer.

[0067] The flexible hard multi-layer nano coating adopts high-power pulsed magnetron sputtering technology (sputtering power 5-10kW, pulse width 2-10μs), combined with high negative bias (-100 ~ -500V), to generate high-energy metal Ti or Cr plasma beams to bombard the surface of the metal bipolar plate, activate the substrate surface and inject it, control the bonding force to enhance the injection layer (thickness 5 ~ 20nm), and then reduce the energy of the metal ions to prepare the metal nano layer, to achieve the injection layer + nano layer, and the overall thickness is maintained at 50-200nm. The advantage of this is to improve the interface bonding between the substrate and the coating, and to construct a multi-layer interface to form crack propagation barriers and stress gradients, thereby reducing the risk of failure caused by stamping crack propagation. Figure 3 As shown, after stamping, no cracks are generated on the surface, and the contact resistance and corrosion current do not decrease, which meets the continuous stamping design requirements of hydrogen fuel cell bipolar plates, and achieves quality preservation, cost reduction, and gain of metal bipolar plates. This method can accurately control the performance of the coating by adjusting the parameters of the micro-pulse, with a fast deposition rate, simple operation, and low cost. In addition, this method does not use flammable and explosive acetylene gas, which is safer and more reliable.

[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a flexible hard nano-ultra-thin coating for continuous stamping of a metal bipolar plate, characterized in that: The following steps are involved: (1) Surface pretreatment of the metal bipolar plate substrate; (2) Loading the sample into the pre-vacuum chamber through the sample loading device, obtaining high-density, high-energy Ti plasma to bombard the surface of the electrode, forming a metal Ti injection layer with a thickness of 5 to 20 nm; (3) changing the high-power pulse parameters to sputtering power of 5 to 10 kW and pulse width of 2 to 10 s, while reducing the ion energy to obtain a high-density plasma with low ion energy, prepare a Ti nanolayer, and form a metallic Ti layer; (4) The metal Ti layer metal bipolar plate substrate is sent into a vacuum chamber to prepare a flexible hard nano multilayer coating.

2. A flexible hard nano ultra-thin coating according to claim 1, characterized in that: The surface pretreatment includes ultrasonic cleaning of the metal bipolar plate, and after cleaning for 10 to 30 minutes, the metal bipolar plate is taken out and dried with nitrogen.

3. The method for preparing a flexible hard nano-ultra-thin coating for continuous stamping of a metal bipolar plate according to claim 1, characterized in that: In step (2), the argon gas pressure is adjusted to 0.1-3 Pa, the flow rate is adjusted to 20-150 sccm, and the pulse parameters are adjusted to 2-10 s.

4. The method for preparing a flexible hard nano-ultra-thin coating for continuous stamping of a metal bipolar plate according to claim 1, characterized in that: In step (3), the gas pressure is adjusted to 0.3-1.5 Pa, the argon gas flow rate is 60-150 sccm, the nitrogen gas flow rate is 20-60 sccm, the pulse parameters are 5-10 kW, and the pulse width is 2-10 μs.

5. The method for preparing a flexible hard nano-ultra-thin coating for continuous stamping of a metal bipolar plate according to claim 1, characterized in that: In step (2) and step (3), the power is 5 to 10 W.

6. The method for preparing a flexible hard nano-ultra-thin coating for continuous stamping of a metal bipolar plate according to claim 1, characterized in that: In step (3), the nitrogen pressure is 0.1Pa to 0.15Pa, and the argon / nitrogen ratio is 4:1 to 8:

1.

7. A flexible hard nano ultra-thin coating for continuous stamping of a metal bipolar plate, comprising a metal bipolar plate substrate, characterized in that The metal bipolar plate substrate is provided with a nano multilayer coating consisting of a bonding layer / functional hard coating, the bonding layer is Cr or Ti metal, and the functional hard coating is a TiC, TiCN, TiN, CrTiN, CrN, CrN / TiN, or CrCTiN nano coating.

8. The flexible hard nano-ultra-thin coating for continuous stamping of metal bipolar plates according to claim 7, characterized in that: The deposition rate of the coating is 20-100 nm / s, the nanohardness is 15-30 GPa, H / E*≥0.1, H 3 / E* 2 ≥0.3, where E* is the effective Young's modulus, Rockwell indentation bonding strength ≥HF1, elastic recovery ≥60%, fracture toughness K IC Greater than 3MPa·m 1 / 2 , contact resistance is less than 5mΩ﹒cm 2 , corrosion current is less than 1μA.

9. The flexible hard nano-ultra-thin coating for continuous stamping of metal bipolar plates according to claim 7, characterized in that: The thickness of the injection layer and the nano layer is 50-200 nm.